CFD modeling for pipeline flow of fine particles at high concentration - Kaushal, D.R.; Thinglas, T.; Tomita, Yuji; Kuchii, Shigeru; Tsukamoto, Hiroshi (International journal of multiphase flow, 2012)
Velocity and slip-velocity distributions, that have never been measured experimentally at such higher concentrations up to 50% by volume, predicted by two-phase Eulerian model are presented for the concentration and velocity ranges covered in this study. Slip velocity between fluid and solids dragged most of the particles in the central core of pipeline, resulting point of maximum concentration to occur away from pipe bottom. Slip-velocity distribution predicted by Eulerian two-phase model. [Display omitted] ► Slip-velocity distributions. ► Slip drags particles away from bottom. ► Maximum concentration occurs away from pipe bottom. Pipeline slurry flow of mono-dispersed fine particles at high concentration is numerically simulated using Mixture and Eulerian two-phase models. Both the models are part of the CFD software package FLUENT. A hexagonal shape and cooper type non-uniform three-dimensional grid is chosen to discretize the entire computational domain, and a control volume finite difference method was used to solve the governing equations. The modeling results are compared with the authors’ experimental data collected in 54.9mm diameter horizontal pipe for concentration profiles at central vertical plane using γ-ray densitometer and pressure drop along the pipeline using differential pressure transducers. Experiments are performed on glass beads with mean diameter of 125μm for flow velocity up to 5m/s and four overall concentrations up to 50% (namely, 0%, 30%, 40% and 50%) by volume for each velocity. The modeling results by both the models for pressure drop in the flow of water are found to be in good agreement with experimental data. For flow of slurry, Mixture model fails to predict pressure drops correctly. The amount of error increases rapidly with the slurry concentration. However, Eulerian model gives fairly accurate predictions for both the pressure drop and concentration profiles at all efflux concentrations and flow velocities. Velocity and slip-velocity distributions, that have never been measured experimentally at such higher concentrations, predicted by Eulerian model are presented for the concentration and velocity ranges covered in this study. Slip velocity between fluid and solids dragged most of the particles in the central core of pipeline, resulting point of maximum concentration to occur away from the pipe bottom.